Radio Show on Books and Libraries as a Means of Promoting the Public Library: Marking the 200th Edition of the Show Tvoja, - Peter Pavletič (Knjižnica)
ABSTRACT Since 2004, the Ciril Kosmač Library of Tolmin has been continuously preparing a radio show on books and libraries on the local radio station Alpski val. The show has been used as an advertising platform or as a means of primary library promotion. The radio show is regarded as one of the tools of what is termed market communication, and it is intended to provide broad public information on the services of a public library, to promote the library’s activities and holdings and to foster a reading culture. The aim of the show is to stimulate the potential user interest in visiting and using the services of a public library, to expand the circle of users and consequently raise the number of visits and library loans. The title of the show, its audio image, target audience, metapromotion and substantive concept are all key to planning the radio show on books and libraries. The radio show is an example of an effective tool that helps to establish the library’s ties with the local community. This example of best practices shows that it is worth pursuing this activity in Slovenia’s public libraries and highlighting it on their websites.